Resurgence as Choice - Shahan, Timothy A. (Behav Processes, 2016)
Resurgence is typically defined as an increase in a previously extinguished target behavior when a more recently reinforced alternative behavior is later extinguished. Some treatments of the phenomenon have suggested that it might also extend to circumstances where either the historic or more recently reinforced behavior is reduced by other non-extinction related means (e.g., punishment, decreases in reinforcement rate, satiation, etc.). Here we present a theory of resurgence suggesting that the phenomenon results from the same basic processes governing choice. In its most general form, the theory suggests that resurgence results from changes in the allocation of target behavior driven by changes in the values of the target and alternative options across time. Specifically, resurgence occurs when there is an increase in the relative value of an historically effective target option as a result of a subsequent devaluation of a more recently effective alternative option. We develop a more specific quantitative model of how extinction of the target and alternative responses in a typical resurgence paradigm might produce such changes in relative value across time using a temporal weighting rule. The example model does a good job in accounting for the effects of reinforcement rate and related manipulations on resurgence in simple schedules where Behavioral Momentum Theory has failed. We also discuss how the general theory might be extended to other parameters of reinforcement (e.g., magnitude, quality), other means to suppress target or alternative behavior (e.g., satiation, punishment, differential reinforcement of other behavior), and other factors (e.g., non-contingent versus contingent alternative reinforcement, serial alternative reinforcement, and multiple schedules).